State owned enterprises leverage as a contingency in public debt sustainability analysis the case of the Peoples Republic of China. - Ferrarini, Benno (Economics Working Papers, 2020)
The leverage of state owned enterprises (SOE) in the Peoples Republic of China (PRC) has grown to a large liability. While there is no room for complacency, there is no need for panic either; even if authorities had to step in to mop up as much as 20% of SOE debt at risk gone bad. This would appear to be manageable at roughly 2.7% of the gross domestic product in 2016 or 5.5% by 2021. The paper demonstrates a method to include SOE debt as a contingent liability in the public debt sustainability assessment framework. The authors of the paper further conclude that while corporate leverage is large, it appears fully manageable.